Transpiration effect on unsteady natural convection boundary layer flow around a vertical slender body - Md Hasanuzzaman; Md Ahasan Kabir; Md Tanvir Ahmed (Results in Engineering, 2021)
In this paper, the transpiration effect on unsteady natural convection boundary layer flow around a vertical slender body has been studied numerically. Applying the similarity transformation together with Boussinesq's approximation, the governing PDEs have been modified into ODEs. These equations have been solved by applying the shooting technique with the help of “ODE45 MATLAB” software. The influences of the pertinent parameters/numbers namely transpiration parameter (FW), the radius of slender body (R0), Prandtl number (Pr) and the driving parameter (β) on the velocity and temperature of the fluid within the boundary layer has been analyzed. The velocity and temperature decrease with increasing the values of the suction parameter but a reverse trend is found for increasing values of blowing parameter from the wall to the free stream. Rising values of the suction parameter (0.5–1.0) increase the local skin friction and the heat transfer rate by approximately about 35% and 31%. The velocity of the fluid decreases for uplifting values of the kinematic viscosity. When the thermal conductivity decreases then the temperature of the fluid decreases. Rising values of the body radius parameter the skin-friction and the rate of heat transfer increase.